Rapid binge-like eating and body weight gain driven by zona incerta GABA neuron activation - Zhang, Xiaobing; van den Pol, Anthony N. (Science (American Association for the Advancement of Science), 2017)
The neuronal substrate for binge eating, which can at times lead to obesity, is not clear. We find that optogenetic stimulation of mouse zona incerta (ZI) γ-aminobutyric acid (GABA) neurons or their axonal projections to paraventricular thalamus (PVT) excitatory neurons immediately (in 2 to 3 seconds) evoked binge-like eating. Minimal intermittent stimulation led to body weight gain; ZI GABA neuron ablation reduced weight. ZI stimulation generated 35% of normal 24-hour food intake in just 10 minutes. The ZI cells were excited by food deprivation and the gut hunger signal ghrelin. In contrast, stimulation of excitatory axons from the parasubthalamic nucleus to PVT or direct stimulation of PVT glutamate neurons reduced food intake. These data suggest an unexpected robust orexigenic potential for the ZI GABA neurons.